Hadith #2602 - Sahih al-Bukhari - Marwan and Al-Miswar bin Makhrama (Sahih al-Bukhari)
(from the companions of Allah’s Messenger (ﷺ)) When Suhail bin `Amr agreed to the Treaty (of Hudaibiya), one of the things he stipulated then, was that the Prophet (ﷺ) should return to them (i.e. the pagans) anyone coming to him from their side, even if he was a Muslim; and would not interfere between them and that person. The Muslims did not like this condition and got disgusted with it. Suhail did not agree except with that condition. So, the Prophet (ﷺ) agreed to that condition and re
Grade: Sahih

Hadith #2603 - Sahih al-Bukhari - 'Urwa on the authority of 'Aisha (Sahih al-Bukhari)
Aisha told me, “Allah’s Messenger (ﷺ) used to examine them according to this Verse: “O you who believe! When the believing women come to you, as emigrants test them . . . for Allah is Oft- Forgiving, Most Merciful.” (60.10-12) Aisha said, “When any of them agreed to that condition Allah’s Apostle would say to her, ‘I have accepted your pledge of allegiance.’ He would only say that, but, by Allah he never touched the hand of any women (i.e. never shook hands with them) while tak
Grade: Sahih

Hadith #2604 - Sahih al-Bukhari - Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي (Sahih al-Bukhari)
When I gave the pledge of allegiance to Allah’s Messenger (ﷺ) and he stipulated that I should give good advice to every Muslim.
Grade: Sahih

Hadith #2605 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
I gave the pledge of allegiance to Allah’s Messenger (ﷺ) for offering the prayers perfectly paying the Zakat and giving good advice to every Muslim.
Grade: Sahih

Hadith #2606 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “If someone sells pollinated date-palms, their fruits will be for the seller, unless the buyer stipulates the contrary.”
Grade: Sahih

Hadith #2607 - Sahih al-Bukhari - 'Urwa on the authority of 'Aisha (Sahih al-Bukhari)
Aisha told me that Barirah came to seek her help in writing for emancipation and at that time she had not paid any part of her price. `Aisha said to her, “Go to your masters and if they agree that I will pay your price (and free you) on condition that your Wala’ will be for me, I will pay the money.” Barirah told her masters about that, but they refused, and said, “If `Aisha wants to do a favor she could, but your Wala will be for us.” Aisha informed Allah’s Messenger (ﷺ) of that a
Grade: Sahih

Hadith #2608 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
While I was riding a (slow) and tired camel, the Prophet (ﷺ) passed by and beat it and prayed for Allah’s Blessings for it. The camel became so fast as it had never been before. The Prophet (ﷺ) then said, “Sell it to me for one Uqiyya (of gold).” I said, “No.” He again said, “Sell it to me for one Uqiyya (of gold).” I sold it and stipulated that I should ride it to my house. When we reached (Medina) I took that camel to the Prophet (ﷺ) and he gave me its price. I returned hom
Grade: Sahih

Hadith #2609 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Ansar said to the Prophet, “Divide our date-palms between us and our emigrant brothers.” The Prophet said, “No.” The Ansar said to the emigrants, “You may do the labor (in our gardens) and we will share the fruits with you.” The emigrants said, “We hear and obey.”
Grade: Sahih

Hadith #2610 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) gave the land of Khaibar to the Jews on the condition that they would work on it and cultivate it and they would get half of its yield.
Grade: Sahih

Hadith #2611 - Sahih al-Bukhari - Uqba bin 'Amir al-Juhayni (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “From among all the conditions which you have to fulfill, the conditions which make it legal for you to have sexual relations (i.e. the marriage contract) have the greatest right to be fulfilled.”
Grade: Sahih

Hadith #2612 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
We used to work on the fields more than the other Ansar, and we used to rent the land (for the yield of a specific portion of it). But sometimes that portion or the rest of the land did not give any yield, so we were forbidden (by the Prophet (ﷺ) ) to follow such a system, but we were allowed to rent the land for money.
Grade: Sahih

Hadith #2613 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ﷺ) said, “No town-dweller should sell for a bedouin. Do not practice Najsh (i.e. Do not offer a high price for a thing which you do not want to buy, in order to deceive the people). No Muslim should offer more for a thing already bought by his Muslim brother, nor should he demand the hand of a girl already engaged to another Muslim. A Muslim woman shall not try to bring about The divorce of her sister (i.e. another Muslim woman) in order to take her place herself.”
Grade: Sahih

Hadith #2614 - Sahih al-Bukhari (Sahih al-Bukhari)
A bedouin came to Allah’s Messenger (ﷺ) and said, “O Allah’s apostle! I ask you by Allah to judge My case according to Allah’s Laws.” His opponent, who was more learned than he, said, “Yes, judge between us according to Allah’s Laws, and allow me to speak.” Allah’s Messenger (ﷺ) said, “Speak.” He (i .e. the bedouin or the other man) said, “My son was working as a laborer for this (man) and he committed illegal sexual intercourse with his wife. The people told me that
Grade: Sahih

Hadith #2615 - Sahih al-Bukhari - Aiman Al-Makki (Sahih al-Bukhari)
When I visited Aisha she said, “Barirah who had a written contract for her emancipation for a certain amount came to me and said, “O mother of the believers! Buy me and manumit me, as my masters will sell me.” Aisha agreed to it. Barirah said, ‘My masters will sell me on the condition that my Wala will go to them.” Aisha said to her, ‘Then I am not in need of you.’ The Prophet (ﷺ) heard of that or was told about it and so he asked Aisha, ‘What is the problem of Barirah?’ He s
Grade: Sahih

Hadith #2616 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) forbade (1) the meeting of the caravan (of goods) on the way, (2) and that a residing person buys for a bedouin, (3) and that a woman stipulates the divorce of the wife of the would-be husband, (4) and that a man tries to cause the cancellation of a bargain concluded by another. He also forbade An-Najsh (see Hadith 824) and that one withholds the milk in the udder of the animal so that he may deceive people on selling it.
Grade: Sahih

Hadith #2617 - Sahih al-Bukhari - Ubayy ibn Ka'b (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Moses the Messenger of Allah,” and then he narrated the whole story about him. Al-Khadir said to Moses, “Did not I tell you that you can have no patience with me.” (18.72). Moses then violated the agreement for the first time because of forgetfulness, then Moses promised that if he asked Al-Khadir about anything, the latter would have the right to desert him. Moses abided by that condition and on the third occasion he intentionally asked Al-Khadir and cau
Grade: Sahih

Hadith #2618 - Sahih al-Bukhari - 'Urwa on the authority of 'Aisha (Sahih al-Bukhari)
Aisha said, “Barirah came to me and said, ‘My people (masters) have written the contract for my emancipation for nine Awaq ) of gold) to be paid in yearly installments, one Uqiyya per year; so help me.” Aisha said (to her), “If your masters agree, I will pay them the whole sum provided the Wala will be for me.” Barirah went to her masters and told them about it, but they refused the offer and she returned from them while Allah’s Messenger (ﷺ)s was sitting. She said, “I presented
Grade: Sahih

Hadith #2619 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
When the people of Khaibar dislocated `Abdullah bin `Umar’s hands and feet, `Umar got up delivering a sermon saying, “No doubt, Allah’s Messenger (ﷺ) made a contract with the Jews concerning their properties, and said to them, ‘We allow you (to stand in your land) as long as Allah allows you.’ Now `Abdullah bin `Umar went to his land and was attacked at night, and his hands and feet were dislocated, and as we have no enemies there except those Jews, they are our enemies and the only
Grade: Sahih

Hadith #2620 - Sahih al-Bukhari - al-Miswar bin Makhrama bin Nawfal (Sahih al-Bukhari)
(whose narrations attest each other) Allah’s Messenger (ﷺ) set out at the time of Al-Hudaibiya (treaty), and when they proceeded for a distance, he said, “Khalid bin Al-Walid leading the cavalry of Quraish constituting the front of the army, is at a place called Al-Ghamim, so take the way on the right.” By Allah, Khalid did not perceive the arrival of the Muslims till the dust arising from the march of the Muslim army reached him, and then he turned back hurriedly to inform Quraish. The
Grade: Sahih

Hadith #2621 - Sahih al-Bukhari - Az-Zuhri from Malik bin Aus (Sahih al-Bukhari)
`Urwa said, “Aisha told me that Allah’s Messenger (ﷺ) used to examine the women emigrants. We have been told also that when Allah revealed the order that the Muslims should return to the pagans what they had spent on their wives who emigrated (after embracing Islam) and that the Muslims should not keep unbelieving women as their wives, `Umar divorced two of his wives, Qariba, the daughter of Abu Umayyah and the daughter of Jarwal Al-Khuza`i. Later on Mu`awiya married Qariba and Abu Jahm ma
Grade: Sahih

Hadith #2622 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) mentioned a person who asked an Israeli man to lend him one-thousand Dinars, and the Israeli lent him the sum for a certain fixed period.
Grade: Sahih

Hadith #2623 - Sahih al-Bukhari - 'Amra bint 'Abdur-Rahman (Sahih al-Bukhari)
Aisha said that Barirah came to seek her help in the writing of her emancipation. `Aisha said to her, “If you wish, I will pay your masters (your price) and the wala’ will be for me.” When Allah’s Messenger (ﷺ) came, she told him about it. The Prophet (ﷺ) said to her, “Buy her (i.e. Barirah) and manumit (free) her, for the Wala is for the one who manumits.” Then Allah’s Messenger (ﷺ) ascended the pulpit and said, “What about those people who stipulate conditions which are n
Grade: Sahih

Hadith #2624 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Allah has ninety-nine names, i.e. one-hundred minus one, and whoever knows them will go to Paradise.” (Please see Hadith No. 419 Vol. 8)
Grade: Sahih

Hadith #2625 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Umar bin Khattab got some land in Khaibar and he went to the Prophet (ﷺ) to consult him about it saying, “O Allah’s Messenger (ﷺ) I got some land in Khaibar better than which I have never had, what do you suggest that I do with it?” The Prophet (ﷺ) said, “If you like you can give the land as endowment and give its fruits in charity.” So `Umar gave it in charity as an endowment on the condition that would not be sold nor given to anybody as a present and not to be inherited, but i
Grade: Sahih